Praktik Hukuman Mati dari Sudut Pandang Ensiklik Veritatis Splendor - Poa, Nicholaus Damianus (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
This article examines the practice of capital punishment from the perspective of the encyclical Veritatis Splendor, a moral document issued by Pope John Paul II in 1993. The article focuses on the moral teachings of the Catholic Church. The Church, as expressed in Veritatis Splendor, considers capital punishment to be inconsistent with human dignity and the core principles of Christian morality. The encyclical emphasizes that human life holds intrinsic value because it is created in the image of God, and that capital punishment violates the fundamental moral principle of the right to life. This theological reflection begins with a discussion of natural law inherent to human beings and follows Jesus' command to a rich young man that the highest good can only be found through a relationship with God. The article then highlights the human freedom to obey the truth and moral law, which guide individuals toward the true good, which is God. In the context of capital punishment, the misuse of human freedom to kill is considered an intrinsically evil act (intrinsece malum), which can never be justified, even with pragmatic reasons such as deterrence or justice. In summary, Veritatis Splendor stresses that every human action, including within the criminal justice system, must be directed toward the true good and respect for human dignity, rejecting capital punishment as a morally contradictory act to the Christian faith.